The innovator's toolkit : 50+ techniques for predictable and sustainable organic growth - Silverstein, David, 1965-; Samuel, Philip; DeCarlo, Neil. (Hoboken, N.J. : John Wiley & Sons, 2009)
An innovation guide for business leaders, managers, and new product developers. The Innovator's Toolkit explains all the fundamental tools and concepts anyone involved in innovation should be familiar with--especially methods and strategies for improving products and services and developing new ones. This book is written in an easy-to-use reference format that helps readers understand why, when, and how to apply each tool. The tools and techniques in this book are organized around a four-step innovation methodology--define, discover, develop, and demonstrate--that takes readers through problem.
The Innovator's Toolkit: 50+ Techniques for Predictable and Sustainable Organic Growth; Contents; Downloadable Exhibits; Preface; Ackowledgments; Introduction: How to Make Organic Growth an Everyday Event -- Systematizing Your Innovation Process; Part I: DEFINE THE OPPORTUNITY; Part II: DISCOVER THE IDEAS; Part III: DEVELOP THE SOLUTION; Part IV: DEMONSTRATE THE INNOVATION; Index.
Includes bibliographical references and index.
Description based on online resource, title from digital title page (viewed on April 11 2024).
John Wiley and Sons
Keywords: Technological innovations -- Management; New products; Corporations -- Growth; Innovations -- Gestion; Entreprises -- Croissance; x; BUSINESS & ECONOMICS -- Structural Adjustment; Corporations -- Growth; New products; Technological innovations -- Management; Innovationsmanagement; Innovationsprozess; Methode; Unternehmen; Vernieuwing; Organisatieontwikkeling; Methodologie